Secondary adjustments and related aspects of transfer pricing corrections : proceedings of a seminar held in Toronto, Canada, in 1994 during the 48th Congress of the International Fiscal Association.: proceedings of a seminar held in Toronto, Canada, in 1994 during the 48th Congress of the International Fiscal Association. (2016) - Unknown
No abstract available